Duodenal metastasis from lung adenocarcinoma: A rare cause of melena. (2015) - AlSaeed, Eyad Fawzi; Tunio, Mutahir A.; AlSayari, Khalid; AlDandan, Sadiq; Riaz, Khalid
Highlights: Duodenal metastasis. Melena and microcytic anemia. Lung carcinoma. Abstract: Introduction: We report a rare case of duodenal metastasis from primary lung adenocarcinoma presented with history of melena and weight loss. Presentation of case: A 52-year-old smoker man presented with six months history of epigastric pain, melena and weight loss. Esophago-gastroduodenoscopy revealed a 10 mm ulcerative lesion in the fourth part of duodenum. Histopathology of resected lesion showed poorly differentiated adenocarcinoma. Tumor cells showed immunopositivity for cytokeratin-7 (CK7), thyroid transcription factor 1 (TTF-1), and immunonegativity for CK20, Villin, CDX2 and thyroglobulin, supporting the diagnosis of metastatic adenocarcinoma of the lung origin. Computed tomography (CT) of chest revealed left hilar mass encasing the main pulmonary artery associated with ipsilateral hilar and contralateral mediastinal lymphadenopathy. Bronchoscopy assisted biopsy of lung mass confirmed the diagnosis of primary adenocarcinoma. Patient was staged as T4N3M1. After the resection of duodenal metastasis followed by three cycles of cisplatinum based chemotherapy with Bevacizumab, melena resolved completely. Discussion: Duodenal metastases from lung adenocarcinoma are extremely uncommon, and rarely produce symptoms. Most of cases require duodenectomy or pancreatico-duodenectomy for symptomatic relief. For smaller duodenal metastatic lesions (≤1 cm) endoscopic resection is a feasible therapeutic option. Conclusion: Although rare, duodenal metastasis from lung adenocarcinoma should also be included in the differential diagnosis of melena. Smaller lesions (≤1 cm) can safely be managed with endoscopic resection.